PENDEKATAN FAVOR DEFENSIONIS DALAM MEREALISASIKAN HAK TERDAKWA UNTUK MENGHADIRKAN SAKSI ATAU AHLI - Susilo, Erwin; Rafi, Muhammad (Veritas et Justitia, 2024)
According to Article 66 of the Indonesian Criminal Procedure Code, public prosecutors are authorized to summon witnesses or experts to strengthen their case against a defendant. In contrast, the defendant is under no obligation to do the same but retains the right to present witnesses or experts in their defense (Article 65). However, challenges arise when defendants must summon witnesses without the backing of pro justitia status, complicating the legitimacy of such summonses. Employing a normative legal approach, it analyzes relevant laws, doctrines, norms, and practices to address the legal inadequacies surrounding the defendant’s right to present exculpatory witnesses or experts, utilizing the Favor Defensionis (FD) doctrine to address these challenges. Key findings include the following: 1) witnesses and experts play a vital role in ensuring verdicts are based on substantive truth, thereby affirming the defendant’s right to present a defense in line with equality of arms and due process principle; 2) ambiguities regarding the pro justitia legitimacy of defendants’ summonses create hesitation among witnesses or experts, impacting their willingness to appear in court; and 3) the FD doctrine supports legal interpretations that favor the defendant to maintain judicial balance. Under this doctrine, public prosecutors should summon witnesses or experts at the request of the defendant or the judge, with judges authorized to order such actions. This approach enables judges’ active judicial participation while preserving defendant’s right to independently call witnesses or experts to support their defense.